2020
DOI: 10.1016/j.ekir.2020.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Predictive Equations and Biochemical Measures Quantifying Net Endogenous Acid Production and the Potential Renal Acid Load

Abstract: Introduction: A limited number of studies have assessed the accuracy and precision of methods for determining the net endogenous acid production (NEAP) and its components. We aimed to investigate the performance of methods quantifying the diet dependent acid-base load. Methods: Data from metabolic balance studies enabled calculations of NEAP according to the biochemical measures (of net acid excretion [NAE], urinary net endogenous acid production [ U NEAP], and urinary potential renal acid load [ U PRAL]) as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…The reader is referred to the work of Parmenter et al for additional background information on all three employed formulas [ 48 , 49 ]. Negative DAL scores (PRAL R < 0 mEq/d) indicate an alkaline-forming potential, whereas positive scores (PRAL R > 0 mEq/d) indicate an acid-forming potential.…”
Section: Methodsmentioning
confidence: 99%
“…The reader is referred to the work of Parmenter et al for additional background information on all three employed formulas [ 48 , 49 ]. Negative DAL scores (PRAL R < 0 mEq/d) indicate an alkaline-forming potential, whereas positive scores (PRAL R > 0 mEq/d) indicate an acid-forming potential.…”
Section: Methodsmentioning
confidence: 99%
“…We refer the reader to the work of Parmenter et al, for additional background information on all scores [ 14 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the authors neither reported total energy intake nor protein intake [ 13 ]. Both are important determinants of DAL and necessary to understand the effects of a particular diet on acid–base homeostasis [ 14 , 15 , 16 ]. Replacing cereals with other cereals per se does hypothetically not affect DAL ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The secondary mechanism that the body uses to deal with a longer term excessively acidic state is to excrete acids via the kidneys (in urine), via saliva, and through the skin (in sweat) [11,18] and to reabsorb bicarbonate. If excess alkalinity is present, the kidneys excrete more bicarbonate into the urine [16,17,19,20].…”
Section: Basic Acid-base Issuesmentioning
confidence: 99%
“…Table 1 provides a categorized list of foods and drinks based on the effect they are thought to have on body pH (based on likely impact of metabolic residues). In each case, we have chosen the most reliable available data in the literature and performed a qualitative comparison based on agreements between the different references [19,20,41,42,46,52,53,71]. However, most of these data came from sources which used measurement methods that have not been verified.…”
Section: Determining Whether Foods Are Acid or Alkaline Formingmentioning
confidence: 99%